2015
DOI: 10.1007/s10562-015-1597-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Lutein Esters by Using a Reusable Lipase-Pluronic Conjugate as the Catalyst

Abstract: An enzymatic route to synthesize lutein esters was investigated using a lipase-Pluronic conjugate as the catalyst. For the synthesis of lutein palmitate, the enzymatic process gave a conversion of 85 % for lutein and a product purity of 96 % at 50°C within 12 h, whereas the free lipase catalyzed process achieved a conversion below 10 %. To demonstrate the generality of this enzymatic process, lutein laurate, lutein myristate and lutein stearate were also synthesized achieving conversions of 73.8, 88.5, 84.4 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…In conclusion, DMF is the best candidate for esterication and activity expression of CALB. The results reveal that as a less toxic and polluting solvent, DMF is more suitable for enzyme reaction of edible substrates 16,17 and can be employed to replace the commonly used polluted and toxic reagents for lutein esterication.…”
Section: Factors In the Immobilization Of G-c 3 N 4 -Ns-pei-mentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, DMF is the best candidate for esterication and activity expression of CALB. The results reveal that as a less toxic and polluting solvent, DMF is more suitable for enzyme reaction of edible substrates 16,17 and can be employed to replace the commonly used polluted and toxic reagents for lutein esterication.…”
Section: Factors In the Immobilization Of G-c 3 N 4 -Ns-pei-mentioning
confidence: 99%
“…14,15 However, very few papers have described the enzymatic synthesis of lutein esters. Wang 16 and Hou 17 tried to catalyze the synthesis of lutein palmitate by Novozyme 435 and lipase-Pluronic F-127. Nevertheless, in their studies, toluene, methyl tert-butyl ether (MTBE), or methyl isobutyl ketone (MIBK) were used as the solvent for lutein esterication, which are not suitable for food applications.…”
Section: Introductionmentioning
confidence: 99%
“…The commercial production of lutein through the chemical synthesis method has not been viable due to poor overall yield. However, the technology news of the University of Maryland, USA reported that their researchers have published a chemical synthesis method for lutein with overall yields >20% from readily available precursor molecules [43,44]. At present, most of the commercially produced carotenoids are produced chemically and only a small portion are obtained from the biotechnological process, including extraction from microalgae, but not lutein by either method.…”
Section: Synthetic Production Of Luteinmentioning
confidence: 99%
“…The CALB-Pluronic-catalyzed conversion of lutein to lutein palmitate was 85.1% at 50 °C in methyl tert-butyl ether, whereas the free lipase only achieved 10% conversion. Lutein laurate, luteinmyristate, and lutein stearate were also successfully synthesized via similar processes, with conversions of 73.8%, 88.55%, and 84.4%, respectively [58].…”
Section: Enzyme-polymer Nanogels Prepared Via Grafting-to Processmentioning
confidence: 98%
“…CALB-Pluronic was successfully used in the esterification of lutein (Fig. 14) [58]. Lutein esters are widely used as an essential human dietary supplement.…”
Section: Enzyme-polymer Nanogels Prepared Via Grafting-to Processmentioning
confidence: 99%